The Power of Object(s) : Design Bestsellers in Belgium - Borka, Max; De Peuter, Patricia (Brussel : MAD Brussels : ING België, 2014)
Bautier, Marina ; Berteau, Alain ; BIG-GAME ; Boo, Bram ; Dewez, Nathalie ; D'Or, Jean-François ; Duffeleer, Anthony ; El-Asmar, Nedda ; Enthoven, Axel ; Gilles, Alain ; Grosemans, Davy ; Jalet, Vincent ; Kaisin, Charles ; Lens, Bart ; Lust, Xavier ; Reniers, Christa ; Schöning, Stefan ; Steverlynck, Diane ; Stockmans, Piet(er) ; Van Severen, Maarten ; Venlet, Danny ; Vincent, Luc ; Willenz, Sylvain ; Wynants, Dirk ; Young, Michael
The Power of Object(s). Design Bestsellers in Belgium, ING Art Center. Hotel Coudenberg, Brussel, 04.09.2014-11.01.2015
boek